2009
DOI: 10.1080/13803390802508918
|View full text |Cite
|
Sign up to set email alerts
|

The Item-Specific Deficit Approach to evaluating verbal memory dysfunction: Rationale, psychometrics, and application

Abstract: In the current study, we introduce the Item-Specific Deficit Approach (ISDA), a novel method for characterizing memory process deficits in list-learning data. To meet this objective, we applied the ISDA to California Verbal Learning Test (CVLT) data collected from a sample of 132 participants (53 healthy participants and 79 neurologically compromised participants). Overall, the ISDA indices measuring encoding, consolidation, and retrieval deficits demonstrated advantages over some traditional indices and indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 57 publications
2
46
1
Order By: Relevance
“…There are several limitations in this study. it has been suggested that measures derived from list learning tasks such as the CvLT-ii may not accurately dissociate the processes of encoding, consolidation and retrieval (Wright et al 2009), and are not reflective of functioning in specific brain regions. While this is an important caveat to our analytical approach, here we classified list-learning indices by the general pattern displayed by patients with frontal vs. MT pathology (Tierney et al 2011;Wolk and dickerson 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations in this study. it has been suggested that measures derived from list learning tasks such as the CvLT-ii may not accurately dissociate the processes of encoding, consolidation and retrieval (Wright et al 2009), and are not reflective of functioning in specific brain regions. While this is an important caveat to our analytical approach, here we classified list-learning indices by the general pattern displayed by patients with frontal vs. MT pathology (Tierney et al 2011;Wolk and dickerson 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have found that distinct ‘frontal’ and ‘temporal’ components contribute to deficits in various forms of memory following severe TBI (Schmitter-Edgecombe & Wright, 2003; Schmitter-Edgecombe & Wright, 2004; Schmitter-Edgecombe et al, 2004; Wright & Schmitter-Edgecombe, 2011; Wright et al, 2010). For example, in a study of verbal memory where we employed a novel item analytic technique for discerning process disruptions on list-learning tests (Wright et al, 2009), we found that severe acceleration-deceleration TBI related-memory deficits were driven by strategic encoding deficits (primary) and consolidation problems (secondary) (Wright et al, 2010). Additionally, our data indicated that while these encoding and consolidation deficits interacted, they made significant independent contributions to the memory impairments observed in our TBI sample.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with its predominant frontostriatal pathology, the memory profile associated with HIV infection is best characterized as a mixed encoding/retrieval profile. The Item-Specific Deficit Approach (ISDA) was developed by Wright et al (2009) to elicit indices of Encoding, Consolidation, and Retrieval from the well-validated California Verbal Learning Test (CVLT; Delis et al, 1987; 2000). The current study evaluated construct validity of the ISDA for the CVLT-II in 40 persons with HIV-associated neurocognitive disorders (HIV+/HAND+), 103 HIV-infected persons without HAND (HIV+/HAND−), and 43 seronegative comparison subjects (HIV−).…”
mentioning
confidence: 99%